The New Frontiers of Fashion Law - Cerchia, Rossella Esther; Pozzo, Barbara (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Fashion law encompasses a wide variety of issues that concern an article of clothing or a fashion accessory, starting from the moment they are designed and following them through distribution and marketing phases, all the way until they reach the end-user. Contract law, intellectual property, company law, tax law, international trade, and customs law are of fundamental importance in defining this new field of law that is gradually taking shape. This volume focuses on the new frontiers of fashion law, taking into account the various fields that have recently emerged as being of great interest for the entire fashion world: from sustainable fashion to wearable technologies, from new remedies to cultural appropriation to the regulation of model weight, from advertising law on the digital market to the impact of new technologies on product distribution. The purpose is to stimulate discussion on contemporary problems that have the potential to define new boundaries of fashion law, such as the impact of the heightened ethical sensitivity of consumers (who increasingly require effective solutions), that a comparative law perspective renders more interesting. The volume seeks to sketch out the new legal fields in which the fashion industry is getting involved, identifying the new boundaries of fashion law that existing literature has not dealt with in a comprehensive manner.